Perancangan alat berkebun hidroponik berbasis musik untuk apartemen tipe studio - Iqbal, Muhammad; Prasetya, Rahmawan Dwi; Adita, Sekar (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
The fast pace of urbanisation in big cities, especially in Indonesia, demands an efficient and practical gardening solution for people with limited space. This research aims to develop an indoor hydroponic installation product design that can be used by beginners, taking into account the factors of ease of use, functionality, and pleasant user experience. The developed prototype integrates music technology as an additional element that serves to create an atmosphere of relaxation, which also supports plant health and improves the user's mental well-being. Using a user-friendly design approach and based on minimalist and industrial design trends, the product was designed to fit into limited spaces such as studio apartments. Product testing was conducted with experienced hydroponic practitioners and potential novice users to test the ease of installation, functionality, and effectiveness of the features. The test results showed that the product provides ease of use and maintenance, as well as providing an enjoyable gardening experience. Thus, this product not only provides a practical solution in hydroponic gardening, but also improves the quality of life of its users through its functional design and relaxing musical elements..